(untitled) (Colombia Medica, 2014)
Objective:To analyze the self-reported perceived health related to socio-demographic characteristics, social health inequalities and social capital in Colombia. Methods:This study is a cross-sectional design; data was obtained from the National Health Survey of Colombia 2007. Independent variables: socio-demographic characteristics; component variables: social health inequality and social capital. Dependent variable: self-reported health. Analysis of the relationship used logistic regression through OR and its confidence interval. Results:The determinant factors for a negative health perceptions are related to being a female (OR: 0.49 [0.47 to 0.52]), and in both genders being older than 37 years of age (OR: 0.72 [0.61 to 0, 85]), living without a partner, black ethnicity, indigenous women (0.80 [0.69 to 0.94] and low economic incomes. Discussion:The relationship between social determinants and social capital in the perception of health shows inequities and indirectly reflects the level of health. Given the policies and the model of health, requires a rational adjustment of the goals, programs, and national and regional strategies with the object of improving the demand and quality of services.